2001
DOI: 10.1128/aem.67.12.5474-5481.2001
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Induced during Adaptation of Acetobacter aceti to High Acetate Concentrations

Abstract: As a typical product of microbial metabolism, the weak acid acetate is well known for its cytotoxic effects. In contrast to most other microbes, the so-called acetic acid bacteria can acquire significant resistance to high acetate concentrations when properly adapted to such hostile conditions. To characterize the molecular events that are associated with this adaptation, we analyzed global protein expression levels during adaptation of Acetobacter aceti by two-dimensional gel electrophoresis. Adaptation was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…It has been reported that the optimum pH for the growth of acetic acid bacteria is 5.5-6.3 (Holt et al, 1994). A. aceti can adapt to high acetic acid conditions by producing 35 proteins specifically induced during acetate adaptation (Steiner et al, 2001). The literature reports that cell numbers of A. aceti decreased faster at pH 3.4 under strictly anaerobic conditions (Joyeux, et al, 1984).…”
Section: Optimization Procedures Using Rsmmentioning
confidence: 99%
“…It has been reported that the optimum pH for the growth of acetic acid bacteria is 5.5-6.3 (Holt et al, 1994). A. aceti can adapt to high acetic acid conditions by producing 35 proteins specifically induced during acetate adaptation (Steiner et al, 2001). The literature reports that cell numbers of A. aceti decreased faster at pH 3.4 under strictly anaerobic conditions (Joyeux, et al, 1984).…”
Section: Optimization Procedures Using Rsmmentioning
confidence: 99%
“…The molecular mechanisms of acetic acid resistance in Acetobacter aceti include adaptation of the cytoplasmic components (9,14) to internal acidification (32), acetic acid efflux via the AatA acetic acid:proton antiporter (31,39), and production of acid-inducible proteins identified by proteomic screens, many with undefined biochemical roles (28,52).…”
mentioning
confidence: 99%
“…A genetic approach identified a gene cluster responsible for acetic acid resistance in Acetobacter aceti, which includes aarA encoding a citrate synthase, aarB encoding a functionally unknown protein, and aarC encoding a protein probably involved in acetic acid assimilation (16,17). A biochemical approach to determine changes in protein profiles in response to acetic acid showed that the production of many proteins was changed (27,38). One of the proteins whose production was enhanced in response to acetic acid was identified as aconitase (27).…”
mentioning
confidence: 99%